2021
DOI: 10.3389/fonc.2021.727778
|View full text |Cite
|
Sign up to set email alerts
|

The Uniqueness of Clear Cell Renal Cell Carcinoma: Summary of the Process and Abnormality of Glucose Metabolism and Lipid Metabolism in ccRCC

Abstract: Kidney cancer is a cancer with an increasing incidence in recent years. Clear cell renal cell carcinoma (ccRCC) accounts for up to 80% of all kidney cancers. The understanding of the pathogenesis, tumor progression, and metastasis of renal carcinoma is not yet perfect. Kidney cancer has some characteristics that distinguish it from other cancers, and the metabolic aspect is the most obvious. The specificity of glucose and lipid metabolism in kidney cancer cells has also led to its being studied as a metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 146 publications
1
36
0
Order By: Relevance
“…Similarly, Hamura et al reported that the modulation of GAA could affect cell proliferation and apoptosis and manipulate chemoresistance in pancreatic cancer cells via malfunctional mitochondria (74). The dysregulated metabolism of glucose in mitochondria is known as an adverse microenvironment in solid tumours, referred to as the Warburg effect, including glucose deprivation and lactic acidosis, potentially resulting in an elevated glycolytic activity in tumour cells (75)(76)(77)(78). Yan et al showed that glucose metabolic reprogramming improves SCLC cell proliferation and metastasis, suggesting it could be a potential regulatory strategy interfering with glucose metabolism in SCLC (56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Hamura et al reported that the modulation of GAA could affect cell proliferation and apoptosis and manipulate chemoresistance in pancreatic cancer cells via malfunctional mitochondria (74). The dysregulated metabolism of glucose in mitochondria is known as an adverse microenvironment in solid tumours, referred to as the Warburg effect, including glucose deprivation and lactic acidosis, potentially resulting in an elevated glycolytic activity in tumour cells (75)(76)(77)(78). Yan et al showed that glucose metabolic reprogramming improves SCLC cell proliferation and metastasis, suggesting it could be a potential regulatory strategy interfering with glucose metabolism in SCLC (56).…”
Section: Discussionmentioning
confidence: 99%
“…Yan et al showed that glucose metabolic reprogramming improves SCLC cell proliferation and metastasis, suggesting it could be a potential regulatory strategy interfering with glucose metabolism in SCLC (56). Considering the function of GAA, which catalyses the production of glucose from glycogen in lysosomes, altering the GAA expression or genetic status could inhibit tumorigenesis in SCLC through the lysosome pathway (56,(74)(75)(76)(77)(78). Interestingly, the DrugBank analysis showed that the drug targeting GAA was Trastuzumab-deruxtecan.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of body weight appears to reduce the incidence of cancers [ 15 , 16 ]. It appears that renal cell carcinoma can be induced by metabolic changes resulting from numerous mutations within genes which products are involved in the regulation of metabolism, including mutations in the hypoxia pathway as well as the phosphatidylinositol-3-kinase (PI3K)/protein kinase B (Akt)/mammalian target of rapamycin (mTOR) pathway [ 17 , 18 ]. Lipidomic data indicate the enhanced accumulation of cholesterol and triglycerides in RCC cells.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, Gao et al found that the TAZ/WNT10B axis may serve as biomarkers and therapeutic targets for KIRC immunotherapy 31 . Taken together, there are many studies on KIRC, but the current understanding of its pathogenesis, tumor progression, and metastasis is still imperfect, with many of its characteristics differing from other cancers 32 34 . Therefore, finding novel ferroptosis-related targets or pathways for the treatment of KIRC would two-fold curb the high recurrence rate and growing drug resistance of KIRC.…”
Section: Introductionmentioning
confidence: 99%